Gating of Transient Receptor Potential Melastatin 8 (TRPM8) Channels Activated by Cold and Chemical Agonists in Planar Lipid Bilayers - Zakharian, Eleonora (Society for Neuroscience, 2010)
The transient receptor potential melastatin 8 (TRPM8) ion channel is a major sensor of environmental cold temperatures. It is activated by cold and chemical agonists, such as menthol and icilin. The activation of these channels both by cold and cooling agents requires the presence of the membrane phospholipid phosphatidylinositol 4,5-bisphosphate [PI(4,5)P(2)]. The mechanism of TRPM8 activation by physical and chemical factors is unknown, and the involvement of cellular signaling pathways has been considered. Here we have characterized the gating mechanism of the rat TRPM8 reconstituted in planar lipid bilayers and its activation by different stimuli. In this system, the influence of cellular signaling pathways can be excluded. We found that TRPM8 activated by cold exhibits steep temperature dependence [temperature coefficient (Q (10)) of ∼40], and the channel openings are accompanied by large changes in entropy and enthalpy, suggesting a substantial conformation change. TRPM8 channel behavior upon menthol and icilin activation was distinguishable, and the effect of icilin depended on the presence of calcium on the intracellular side of the protein. Here we also demonstrate that PI(4,5)P(2) is the prime factor that impacts the gating of TRPM8 and that other phosphoinositides are less efficient in supporting channel activity. Menthol increases the potency of PI(4,5)P(2) to activate the channels and increases binding of phosphoinositides to the full-length channel protein. Our data demonstrate conclusively that TRPM8 is gated by cold and its chemical agonists directly, and that dependence of its gating on PI(4,5)P(2) is a result of direct specific interactions with the lipid.